THE EFFECT OF SALES GROWTH, LEVERAGE, PROFITABILITY, AND SIZE ON TAX AVOIDANCE: Case Study of Manufacturing Companies Listed on the IDX for the 2019-2022 Period - Galuh Ardyanto; Abi Suryono; Meutia Layli; Kusumaningdiah Retno Setiorini; Citra Amelia Putri (STIE PGRI Dewantara Jombang, 2024)
This research aims to determine the effect of sales growth, leverage, profitability, and size on tax avoidance. The population of this research is manufacturing companies registered on the IDX for the 2019-2022 period, with a sample selection technique using purposive sampling. The analytical method used is multiple linear regression and uses SPSS as a research tool. The results of this research show that sales growth and leverage have a positive effect on tax avoidance, while profitability and company size have a negative effect on tax avoidance.